NOVEL FORMULATION FOR ENHANCED EFFICACY OF LAVANG TAILA (CLOVE OIL) FOR ANTI-INFLAMMATORY ACTIVITY - Kandekar, *Sudhir Moreshwar; Bhujbal, Neha; Deshpande, Yogeshwar (International Journal of Ayurveda and Pharma Research, 2016)
Lavang (Clove - Eugenia caryophyllata) has been used since years for its analgesic, anti-inflammatory and anesthetic effects. The aim of current study was to observe anti-inflammatory activity of clove oil in the form of Bio-adhesive Gel, since it has property to inhibitCOX-2 enzyme and prostaglandins.Self-Micro emulsifying Drug Delivery System (SMEDDS) is an isotropic and thermodynamically stable mixture of oil, surfactant/co-surfactant and drug.  A novel SMEDDS of extract of Clove (Lavanga Taila) and other chemicals as Vitamin E TPGS - as surfactant,  antioxidant, penetration enhancer and can protect the oil from degradation, Transcutol P- as co-surfactant, Ethanol- co-solvent, Carbopol - as the gelling agent and Distilled water.  Carrageenan induced rat paw edema model was used to investigate the in vivo performance. Commercial clove oil formulation was used as reference formulation.After the carrageenan injection, the paw volumes were measured at 15 min, 30 min, 1 hour, 2 hours, 3 hours by using a plethysmometer. The percentage inhibition of edema was calculated by the equation: % inhibition of edema = 100 [1-(Vt/Vc)].Various proportions of the contents were used to prepare several SMEDDS formulations. The optimized batch was selected on the basis of clarity and stability for 24 hrs. Organoleptic parameters such as pH value (7.3), Spreadability (++), Consistency(+++), Washability (+++), Irritation(None), Film formation (continuous) were observed for the prepared gel.Results reveal that the action of SMEDDS gel was about two times better than the clove oil alone, as the percentage of inhibition of edema was 42.06 % by SMEDDS gel while the Clove oil inhibits 25.67% at the end of 3rd hour. The in vivo studies showed that bio-adhesive gel of clove oil has significant role as anti-inflammatory (shothahar) action. The gel can be further used for oral preparations. However more investigations are needed to elucidate the exact mechanism of the gel.